2007
DOI: 10.1055/s-2007-981585
|View full text |Cite
|
Sign up to set email alerts
|

Protective Action of Ilex paraguariensis Extract against Free Radical Inactivation of Paraoxonase-1 in High-Density Lipoprotein

Abstract: Paraoxonase 1 (PON-1), an antioxidant enzyme carried mainly by HDL, has been shown to display cardioprotective effects. In this study, we investigated whether the polyphenol-rich beverage mate, obtained from extract of Ilex paraguariensis (IP), prevented the loss of PON-1 activity from HDL during oxidant stress. The peroxide radical generator 2,2-azobis(2-amidinopropane) dihydrochloride (AAPH) induced time- and dose-dependent oxidation of HDL, as measured by lipoperoxide content, which is accompanied by a para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
2
30
0
9
Order By: Relevance
“…paraguariensis (Aquifoliaceae) tea is widely consumed in South America, especially in Brazil, Argentina and Paraguay. The tea made from the leaves has several phytochemicals such as caffeic acid, chlorogenic acids, 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid, catechins, amino acids, caffeine, quercetin, kaempferol, ascorbic acid, B 1 /B 2 vitamins, and rutin (Carini et al 1998, Dutra the inhibition of high-density lipoprotein (HDL) oxidation induced by peroxyl radicals (Menini et al 2007), inhibitory ability against low-density lipoprotein (LDL) oxidation (Bracesco et al 2003), increase of gene expression of some antioxidant enzymes found in many organs (Matsumoto et al 2009), decrease in the serum concentration of LDL-cholesterol with a respective increase of the serum antioxidant capacity and glutathione content (Arçari et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…paraguariensis (Aquifoliaceae) tea is widely consumed in South America, especially in Brazil, Argentina and Paraguay. The tea made from the leaves has several phytochemicals such as caffeic acid, chlorogenic acids, 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid, catechins, amino acids, caffeine, quercetin, kaempferol, ascorbic acid, B 1 /B 2 vitamins, and rutin (Carini et al 1998, Dutra the inhibition of high-density lipoprotein (HDL) oxidation induced by peroxyl radicals (Menini et al 2007), inhibitory ability against low-density lipoprotein (LDL) oxidation (Bracesco et al 2003), increase of gene expression of some antioxidant enzymes found in many organs (Matsumoto et al 2009), decrease in the serum concentration of LDL-cholesterol with a respective increase of the serum antioxidant capacity and glutathione content (Arçari et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas revelam grande capacidade antioxidante do extrato de erva-mate (BERTÉ et al, 2011;PRECI et al, 2011). Estudos com extrato de erva-mate demonstram a eficácia na ação cardioprotetora (MENINI et al, 2007). O consumo regular de chá mate melhora as defesas antioxidantes por múltiplos mecanismos, tanto pelo aumento da circulação de compostos bioativos, como pela regulação dos mecanismos celulares e enzimáticos que combatem o estresse oxidativo (MATSUMOTO et al, 2009).…”
Section: Introductionunclassified
“…The oxidation process is not yet used for Maté leaves, but could be an alternative to prepare the beverages resembling black tea. Besides the antioxidant properties, Maté has hypocholesterolemic effect due to the reduction of oxidation of low density lipoproteins (LDL), minimizing the formation of atheroma, characteristic attributed to the phenolic constituents in the leaves (Bracesco et al 2003;Menini et al 2007). The concentration of polyphenols in the Maté has a strong correlation with the antioxidant capacity of this product (Chandra and Mejia 2004).…”
Section: Introductionmentioning
confidence: 99%